2010
DOI: 10.1093/carcin/bgq265
|View full text |Cite
|
Sign up to set email alerts
|

CC chemokine ligand 21 enhances the immunogenicity of the breast cancer cell line MCF-7 upon assistance of TLR2

Abstract: CC chemokine ligand 21 (CCL21) is a known attractant for CCR7-positive (CCR7+) cells, but its additional role in the immunogenicity of CCR7+ cells remains poorly understood. This study explored the effects of CCL21-CCR7 ligation on cancer immunogenicity and related antitumor immune response, in the presence and absence of mitomycin C (MMC) treatment. CCL21-CCR7 binding upregulated human leukocyte antigen class I-restricted tumor antigen presentation with increased expression of human leukocyte antigen class I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…46 Indeed, a recent study showed that TLR2 activation promotes breast cancer cell invasiveness and adhesiveness. 52 Moreover, in a melanoma mouse model, TLR2 targeting attenuates pulmonary metastases of tumor, whereas combining an anti-TLR2 antibody and a cytotoxic agent, gemcitabine, provided a further improvement in the survival of tumor-bearing mice. 53 Remarkably, TLR2 stimulation has been shown to sense oxidation-associated molecular patterns, providing a key link connecting inflammation, oxidative stress and innate immunity.…”
Section: Methodsmentioning
confidence: 99%
“…46 Indeed, a recent study showed that TLR2 activation promotes breast cancer cell invasiveness and adhesiveness. 52 Moreover, in a melanoma mouse model, TLR2 targeting attenuates pulmonary metastases of tumor, whereas combining an anti-TLR2 antibody and a cytotoxic agent, gemcitabine, provided a further improvement in the survival of tumor-bearing mice. 53 Remarkably, TLR2 stimulation has been shown to sense oxidation-associated molecular patterns, providing a key link connecting inflammation, oxidative stress and innate immunity.…”
Section: Methodsmentioning
confidence: 99%
“…This process is dependent on the receptor of these chemokines: CCR7 [ 2 , 190 ]. Therefore, the increased expression of these chemokines in a tumor has an anti-cancer effect via cytotoxic TIL [ 195 , 196 , 197 , 198 ].…”
Section: Ccr7 Ccl19 and Ccl21mentioning
confidence: 99%
“…The interaction between CCR7 and CCL21 has been shown to improve the immunogenicity of CCR7-expressing breast cancer cells [85]. It also induces actin polymerization and pseudopodia formation, resulting in increased cell motility as illustrated in (Figure 1) [86].…”
Section: C-c Chemokine Receptor 7 (Ccr7) and Breast Cancermentioning
confidence: 99%
“…Indeed, in vivo CCR7 C-terminal partial truncation decreases the receptor internalization, while maintaining the chemotaxis ability to CCR7 ligands [135], and prevents lymphocyte adhesion and extravasation to the HEVs [136]. Additional studies reported that the intra-tumoral injection of recombinant CCL21 significantly delayed tumor progression and stimulated cytotoxic immune responses [85,137]. Moreover, in vitro experiments have demonstrated that blocking the CCR7 receptor decreases the incidence of metastasis [86,121].…”
Section: Therapy and Future Directionsmentioning
confidence: 99%